A Risky Business? Habitat and Social Behavior Impact Skin and Gut Microbiomes in Caribbean Cleaning Gobies - Xavier, Raquel; Mazzei, Renata; Pérez-Losada, Marcos; Rosado, Daniela; Santos, Joana L.; Veríssimo, Ana; Soares, Marta C. (Frontiers in Microbiology, 2019)
The broadstripe cleaning goby Elacatinus prochilos has two alternative ecotypes: sponge-dwellers, which live in large groups and feed mainly upon nematode parasites; and coral-dwellers, which live in small groups or in solitude and behave as cleaners. Recent studies focusing on the skin and gut microbiomes of tropical fish showed that microbial communities are influenced mainly by diet and host species. Here we compare the skin and gut microbiomes of the Caribbean broadstripe cleaning goby Elacatinus prochilos alternative ecotypes (cleaners and non-cleaners) from Barbados and predict that different habitat use and behavior (cleaning vs non-cleaning) will translate in different microbial assemblages between the two ecotypes. We sequenced the microbial 16S rRNA V4 region and performed amplicon sequence variant (ASV) analysis using the dada2 pipeline implemented in the QIIME 2 bioinformatic platform. We used Linear Regression and permutational multivariate analysis of variance to test whether differences in alpha- and beta-diversities, respectively, could be attributed to ecotype. We found significant differences in both alpha- and beta-diversity of skin and gut microbiomes belonging to different ecotypes. Importantly, the skin microbiome of obligate cleaners is more diverse (alpha-diversity estimates) and harbours a significantly higher proportion and prevalence of potential fish pathogens. Likewise, potential pathogens were also more prevalent in the gut of coral dwellers. We suggest that habitat use, diet, but also direct contact with potential diseased clientele during cleaning, could be the cause for this pattern.